Perancangan Buku Ilustrasi Interaktif Tentang Aksara Jawa Untuk Siswa SD Kelas 3-6 - Semesta, Houri Gita; Romadhona , Mahimma; Arifianto, Pungky Feby (Innovative: Journal Of Social Science Research, 2024)
Javanese script, which is part of Javanese cultural heritage which is important to preserve in the future. However, understanding Javanese script material is still a challenge for most elementary school students, even though it has been taught in the Javanese language curriculum from grades 3 to 6. This is due to its rare use in daily life and the influence of the learning methods applied by teachers. Therefore, there is a need for interactive and fun learning media related to Javanese script. This research uses a qualitative descriptive method by utilizing data from observations, interviews, questionnaires and literature studies. The results of the analysis show that designing an interactive illustrated book based on the story of Aji Saka, which is the story of the origin of Javanese script, can increase children's interest in learning Javanese script. With its interactive features, it is hoped that this book can create an interesting learning experience, engage children's emotions, and help improve their understanding of Javanese script, which will ultimately help in preserving this cultural heritage. Keywords: Javanese Script, Aji Saka, Book Interactive Illustration.